Концептуальні положення забезпечення інформаційної безпеки підприємства - Полозова, Т. В.; Свірщевський, К. О. (ХНУРЕ, 2016)
In this article the enterprise information security concept is made. General steps of information security implementation are considered. The proposal number of obligatory actions for basic information security is made.
Keywords: інформаційна безпека; інформаційна система; політика безпеки підприємства